Framework Administered Account for Selected Fund Activities : Kuwait Subaccount for Selected Fund Activities. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
In March 2009, the Fund established a new Framework Administered Account to administer external financial resources for selected Fund Activities (the 'SFA Instrument'). The financing of activities under the terms of the SFA Instrument is implemented through the establishment and operation of a subaccount within the SFA. This paper requests Executive Board approval to establish the Kuwait Subaccount for Selected Fund Activities (the 'Subaccount') under the terms of the SFA instrument.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fund Member; PP; Subaccount; Terms and Conditions Of The Subaccount; Terms and Conditions; Kuwait